Determinasi Harga Saham Perusahaan Pertambangan - Linda Ratnasari Zalukhu; Syahyunan Syahyunan; Hafriz Rifki Hafas (Pusat Riset Manajemen Dan Publikasi Ilmiah Serta Pengembangan Sumber Daya Manusia, 2022)
This study aims to determine the effect of return on assets, earnings per share and debt to equity ratio on stock prices in companies listed on the Indonesia Stock Exchange. This research is causal associative research and the type of data used is quantitative data. The data used is obtained from the company's financial statements that have been audited on the Indonesia Stock Exchange during the study period. The analytical method used is descriptive analysis and multiple linear regression of panel data. The population of this study is banking companies for the 2016-2020 period, which amounted to 46 companies. The sample in this study amounted to 37 companies. The results of this study indicate that return on assets has a positive and insignificant effect on stock prices, earnings per share has a positive and significant effect on stock prices, debt to equity ratios have a negative and insignificant effect on stock prices. return on assets, earnings per share and debt to equity ratio simultaneously have a positive and significant effect on stock prices.